Densidade básica da madeira de eucalipto em gradientes climáticos no Brasil - Rocha, Sofia Maria Gonçalves (2018)
Genetic planting materials together with environmental conditions determine the productive potential of the site and are of fundamental importance under the quality of the resulting wood, and knowing the behavior of different species under different climatic conditions is essential for forest planning. In this context, the objective of this work was to evaluate the influence of climatic conditions under the density of eucalyptus wood and to verify the potential of property estimation through meteorological variables. The basic wood density of 04 eucalyptus clones was analyzed at 04 years of age in 11 sites in Brazil with different climatic characteristics. The meteorological variables temperature, precipitation, maximum vapor pressure deficit, water deficiency and seasonality of temperature and precipitation were used to characterize the sites regarding their climatic conditions during the growing period. It was carried out the hierarchical grouping of the sites and verified the behavior of the density of the wood within the groups formed. Linear regression equations were adjusted between the most influential meteorological variables under wood density in order to identify the potential estimator for wood density. Four groups were formed and within each one the growth density basic behavior of each clone was verified. In general, drier locations allow higher densities due to a decrease in growth rate, but the behavior is intrinsic to each clone and does not establish a general rule. The maximum DPV and the DEF were the variables most correlated and with the best potential wood density estimators. Although density is an inherited characteristic, there is significant interface with climatic variables.